Platform for laser-driven X-ray diagnostics of heavy-ion heated extreme states of matter - P. Hesselbach; J. Lütgert; V. Bagnoud; R. Belikov; O. Humphries; B. Lindqvist; G. Schaumann; A. Sokolov; A. Tauschwitz; D. Varentsov; K. Weyrich; B. Winkler; et al. (Matter and Radiation at Extremes)
We report on commissioning experiments at the high-energy, high-temperature (HHT) target area at the GSI Helmholtzzentrum für Schwerionenforschung GmbH, Darmstadt, Germany, combining for the first time intense pulses of heavy ions from the SIS18 synchrotron with high-energy laser pulses from the PHELIX laser facility. We demonstrate the use of X-ray diagnostic techniques based on intense laser-driven X-ray sources, which will allow probing of large samples volumetrically heated by the intense heavy-ion beams. A new target chamber as well as optical diagnostics for ion-beam characterization and fast pyrometric temperature measurements complement the experimental capabilities. This platform is designed for experiments at the future Facility for Antiproton and Ion Research in Europe GmbH (FAIR), where unprecedented ion-beam intensities will enable the generation of millimeter-sized samples under high-energy-density conditions.